Staying on campus during MCO a strain on students - Abdullah, Muhammad Faris (New Straits Times, 2020)
RESEARCH in the United Kingdom has found significant depression and significant anxiety have doubled after a Covid-19 lockdown was enforced in the country. A similar situation was also reported in Italy, leading the Italian government to launch a nationwide psychological support programme for those mentally affected by the lockdown. There is already emerging evidence the same thing is happening here.